Faktor Risiko Unsafe Action Pada Pekerja Proyek Pembangunan Apartemen Victoria Tower PT. PP Persero Tbk Bekasi Jawa Barat Tahun 2021 - Dewi Febrianna Indahsari (2021)
Work accidents in the construction sector are high this is caused by worker behavior factors. Unsafe Action is the action of a person who can endanger the worker himself and others who cause work accidents. The purpose of this study was to determine the risk factors associated with unsafe behavior among construction workers of the Victoria Tower Apartment Project. This research is a quantitative research using a cross-sectional research design. The sampling technique used was Total Sampling with a sample size of 75 construction workers. Data analysis in this study is univariate analysis and bivariate analysis using the Chi-Square test. The results of the analysis show that there is a significant relationship between knowledge related to unsafe action (p = 0.000), perceptions of unsafe action (p = 0.000) and the availability of K3 facilities and infrastructure (p = 0.000) with unsafe action and there is no significant relationship between regulations (p = 0.000) p = 0.514) and supervision (p = 0.229) with unsafe action. Therefore, the suggestion for the company is to hold a K3 training program, apply a punishment system. The suggestions for workers include complying with company regulations and participating in a safety briefing program.